Integrated sustainability assessment for a bioenergy system: A system dynamics model of switchgrass for cellulosic ethanol production in the U.S. midwest. (10th October 2019) - Jin, Enze; Mendis, Gamini P.; Sutherland, John W.
Abstract: Cellulosic biofuels produced from energy crops offer significant advantages over first generation biofuels. In order to understand and predict the sustainability performance of cellulosic biofuel development, this study builds a system dynamics model for a biofuel system producing cellulosic ethanol from switchgrass under different scenarios. The model can simulate the dynamic behaviors of the cellulosic biofuel system and quantify its environmental, economic, and social impacts. The projected results indicate that cellulosic ethanol production is economically viable based on advanced bioconversion technologies and can provide significant benefits to the environment, such as greenhouse gas reductions and water use savings. The cellulosic ethanol industry also can make significant contributions to the bioeconomy and social benefits. This study finds that the target of cellulosic biofuels (16 billion gallons by 2022) mandated by the revised Renewable Fuel Standard (RFS2) program cannot be achieved within land-use change constraints, but may be achieved if there is no limitation on the conversion of pasture or cropland to energy crop land. Moreover, nitrate leaching and biodiversity change should be considered when expanding energy crops on marginal land, pasture, and cropland. This model is applicable for other complex bioenergy systems as a sustainability assessment tool and can provide comprehensive insights for stakeholders and policy makers to establish and implement favorable strategies for stimulating cellulosic biofuel development. Highlights: A system dynamics-based sustainability model is applied to a cellulosic ethanol system. Environmental, economic, and social impacts of the cellulosic ethanol system are quantified. It is profitable to produce cellulosic ethanol with advanced bioconversion technologies. Compliance with RFS2 mandate can be achieved with sufficient land allocation for energy crops. Government subsidies can facilitate the commercialization of cellulosic ethanol.